PATIENTS RECEIVING HEMODIALYSIS WITH THE NURSING DIAGNOSIS OF FLUID VOLUME EXCESS: SOCIOECONOMIC AND CLINICAL ASPECTS - Maria Isabel da Conceição Dias Fernandes Cavalcanti; Priscila Kaline de Andrade Silva; Anna Lívia de Medeiros Dantas; Maria das Graças Mariano Nunes de Paiva; Marilia Gabriela de Azevedo Araújo; Ana Luisa Brandão de Carvalho Lira (Universidade Federal do Paraná, 2015)
This study aimed to describe socioeconomic and clinical aspects of chronic kidney patients receiving hemodialysis, with the nursing diagnosis of Fluid Volume Excess. It is a transversal study, undertaken in a teaching hospital and hemodialysis clinic in the Northeast of Brazil, with a sample of 100 patients. Data collection was undertaken using a questionnaire which covered clinical and social economic data, between December 2012 and April 2013. The majority of patients with a diagnosis were female, of mixed African and European descent, retired, with a companion, claimed to follow a religion, had a mean age of 50.4 years old, had studied for a mean of 6.5 years, and had a mean income of two minimum salaries. Furthermore, they had hypertension, azotemia and hyperkalemia, had had kidney disease for a median of 37 months and had been receiving hemodialysis for a median of 33.5 months. They were receiving drug treatment with sevelamer hydrochloride, folic acid, recombinant human erythropoietin and antihypertensive medications. Identifying socioeconomic and clinical aspects contributed to the nursing team's knowledge of the context in which the chronic kidney patients are inserted.